ANALISIS PORTOFOLIO BERBASIS CAPM PADA SAHAM-SAHAM JAKARTA ISLAMIC INDEKS (JII) SELAMA MASA PANDEMI COVID-19 - Naifi Naufal (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze the performance of stock portfolios included in the Jakarta Islamic Index (JII) during the COVID-19 pandemic using the Capital Asset Pricing Model (CAPM). The COVID-19 pandemic has significantly impacted global financial markets, including the Indonesian stock market. Using daily stock price data from January 2020 to June 2023, this study evaluates the risk and returns of JII stock portfolios. CAPM analysis is used to determine whether these stocks provide returns commensurate with the risks taken during the pandemic period. Portfolio analysis was conducted on combinations of ANTM, INCO, ADRO, KLBF, UNTR, PTBA, ICBP, and TLKM stocks, providing a comprehensive view of the expected returns and risks associated with these investments. Using CAPM, the daily expected returns for each portfolio were calculated based on the individual stock betas and the daily market expected returns. The results show variations in expected returns depending on the composition of stocks in the portfolio. Portfolios with combinations of UNTR, PTBA, ICBP and TLKM stocks provided a more favorable risk-return profile compared to other portfolios, making them a more attractive choice for investors seeking a balance between risk and return.